2013
DOI: 10.1186/1477-3155-11-2
|View full text |Cite
|
Sign up to set email alerts
|

3, 4-dihydroxy-L-phenylalanine-derived melanin from Yarrowia lipolytica mediates the synthesis of silver and gold nanostructures

Abstract: BackgroundNanobiotechnology applies the capabilities of biological systems in generating a variety of nano-sized structures. Plants, algae, fungi and bacteria are some systems mediating such reactions. In fungi, the synthesis of melanin is an important strategy for cell-survival under metal-stressed conditions. Yarrowia lipolytica, the biotechnologically significant yeast also produces melanin that sequesters heavy metal ions. The content of this cell-associated melanin is often low and precursors such as L-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 37 publications
3
68
0
1
Order By: Relevance
“…This study suggested that A. auricular melanin inhibits quorum-sensing (QS)-regulated biofilm formation in all strains tested without interfering with their growth [122]. Silver nanoparticles incorporated Yarrowia lipolytica melanin exhibited antimicrobial activity against the pathogen Salmonella paratyphi, and they were also effective at disrupting biofilms on polystyrene as well as glass surfaces [123]. These nanoparticles displayed excellent antifungal properties toward an Aspergillus sp.…”
Section: Biological Activities Of Melaninmentioning
confidence: 95%
See 1 more Smart Citation
“…This study suggested that A. auricular melanin inhibits quorum-sensing (QS)-regulated biofilm formation in all strains tested without interfering with their growth [122]. Silver nanoparticles incorporated Yarrowia lipolytica melanin exhibited antimicrobial activity against the pathogen Salmonella paratyphi, and they were also effective at disrupting biofilms on polystyrene as well as glass surfaces [123]. These nanoparticles displayed excellent antifungal properties toward an Aspergillus sp.…”
Section: Biological Activities Of Melaninmentioning
confidence: 95%
“…Silver nanostructures synthesized with melanin derived from Y. lipolytica displayed excellent antifungal activity against an Aspergillus sp. isolated from a wall surface, indicating its potential application as effective paint additives [123]. The melanin-mediated nanostructures with broad-spectrum antimicrobial activity against food pathogens may be considered suitable for many practical food packaging applications because they can effectively inhibit the growth of pathogens and increase the shelf life of packed food products [124].…”
Section: Medical Applicationsmentioning
confidence: 99%
“…Absent in the spectrum of sample 2 are peaks with wavenumbers between 1,500 and 1,540 cm À1 . Such peaks have been assigned to amino functionalities in melanin pigments derived from DOPA (Apte et al 2013;Tu et al 2009). This further suggests that tyrosine was not built into the pigment sample when mixed with HGA.…”
Section: Discussionmentioning
confidence: 99%
“…Uniform flat melanin films can be obtained with dopamine or other similar precursors by spray deposition, and these thin films show a stacked planar structure with interesting electronic and optical properties [205] to be used as semiconductors in electrically qualified devices and other nanotechnological applications [206]. Yarrowia lipolytica is biotechnologically significant yeast that produces a dopa-melanin used for the synthesis of silver and gold nanostructures effective as paint-additives [207].…”
Section: Melanin Functionsmentioning
confidence: 99%